Preliminary evidence of nocturnal transpiration and stomatal conductance in potato and their interaction with drought and yield - Ramírez, D.; Yactayo, W.; Rolando, J.L.; Quiróz, R. (Springer, 2017)
In spite of the growing evidence showing the occurrence of nocturnal water exchange measured by stomatal conductance (SCnight, related to stomatal openness) and transpiration (TRnight, related to water losses) in different crops, how those processes are affected by soil water availability is still unknown. A preliminary study was conducted to test the occurrence of TRnight and SCnight (assessed in two moments) in two potato cultivars (UNICA and Sarnav), subjected to a long-term water restriction. The overall TRnight average were 9.0 ± 0.6 and 5.4 ± 2.6% for total daily transpiration under well-watered and water restricted conditions, respectively. Cultivar differences in early night and predawn SCnight and TRnight were more evident under non-restricted water conditions. Tuber yield was linearly correlated with TRnight and predawn and early-night SCnight. These preliminary findings emphasize the need for future research to corroborate the detection of TRnight and SCnight under water restrictions in potato, addressing the functional implications of these traits and the usefulness of SCnight for screening large sets of genotypes for potato breeding.